Bimetal-organic framework nanoboxes enable accelerated redox kinetics and polysulfide trapping for lithium-sulfur batteries - Zhu, Zhuo (2023)
Lithium-sulfur (Li−S) batteries are considered as promising candidates for next-generation energy storage systems in view of the high theoretical energy density and low cost of sulfur resources. The suppression of polysulfide diffusion and promotion of redox kinetics are the main challenges for Li−S batteries. Herein, we design and prepare a novel type of ZnCo-based bimetallic metal–organic framework nanoboxes (ZnCo-MOF NBs) to serve as a functional sulfur host for Li−S batteries. The hollow architecture of ZnCo-MOF NBs can ensure fast charge transfer, improved sulfur utilization, and effective confinement of lithium polysulfides (LiPSs). The atomically dispersed Co−O4 sites in ZnCo-MOF NBs can firmly capture LiPSs and electrocatalytically accelerate their conversion kinetics. Benefiting from the multiple structural advantages, the ZnCo-MOF/S cathode shows high reversible capacity, impressive rate capability, and prolonged cycling performance for 300 cycles.